2023
DOI: 10.1088/1748-0221/18/09/p09039
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting radio frequency linear collider HELEN

S. Belomestnykh,
P.C. Bhat,
A. Grassellino
et al.

Abstract: This article discusses a proposed Higgs-Energy LEptoN (HELEN) e + e - linear collider based on advanced traveling wave superconducting radio frequency technology. The proposed collider offers cost and AC power savings, smaller footprint (relative to the ILC), and could be built at Fermilab. After the initial physics run at 250 GeV, the collider could be upgraded either to higher luminosity or to higher, up to 500 GeV, energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…• linear colliders based on high gradient SRF (in the accelerating gradient range of 50 MV/m to 90 MV/m; standing wave or travelling wave structures). A center of mass energy reach between 250 and 500 GeV with the facility's central campus within the Fermilab site is possible [36],…”
Section: Emerging Concepts and Proposalsmentioning
confidence: 99%
See 2 more Smart Citations
“…• linear colliders based on high gradient SRF (in the accelerating gradient range of 50 MV/m to 90 MV/m; standing wave or travelling wave structures). A center of mass energy reach between 250 and 500 GeV with the facility's central campus within the Fermilab site is possible [36],…”
Section: Emerging Concepts and Proposalsmentioning
confidence: 99%
“…Since the ILC SRF linac parameters were baselined in 2013 [40,43], the community has made advances in further developing the technology. Three possible paths have been identified that could lead to a more compact SRF linear collider, the Higgs-Energy LEptoN (HELEN) collider [36,65]. The options are listed here in the order of their maturity:…”
Section: Helen -A Linear Collider Based On Advanced Srfmentioning
confidence: 99%
See 1 more Smart Citation